2016
DOI: 10.1097/mbc.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in patients with von Willebrand disease

Abstract: Von Willebrand disease (vWD) is the most common inherited bleeding disorder. The biggest challenge in the management of vWD is the difficulty in performing surgical procedures because of bleeding. Treatment guidelines recommend the use of pure von Willebrand factor or von Willebrand factor/factor VIII (vWF/FVIII) concentrate in patients with type 2 or type 3 vWD undergoing surgery, in patients with type 1 vWD undergoing surgery who are unresponsive, and in patients for whom desmopressin acetate is contraindica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
(17 reference statements)
0
18
0
2
Order By: Relevance
“…Adjunctive therapies, such as intravenous immunoglobulins and tranexamic acid, have also been reported. [7,8] Although current measures to mitigate surgical bleeding in WVD appear to be safe and well tolerated in small series, effects of pharmacology on perioperative thrombotic risks remain uncertain. [79]…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive therapies, such as intravenous immunoglobulins and tranexamic acid, have also been reported. [7,8] Although current measures to mitigate surgical bleeding in WVD appear to be safe and well tolerated in small series, effects of pharmacology on perioperative thrombotic risks remain uncertain. [79]…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Patients with VWD are also exposed to a higher risk of future bleeding complications from pregnancy, childbirth, surgical and dental procedures, and minor injuries, which can be managed with appropriate intervention following diagnosis. [14][15][16] We showed recently, through longitudinal analysis of medical insurance claims data from a commercially insured US population, that VWD patients' need for bleed care (number of medical claims for VWD or bleeding events and prescription claims) was substantially reduced after (vs before) VWD diagnosis. 17 However, misrecognition of VWD was common, with a quarter of patients visiting the same health care specialty for episodic bleed care at least twice before diagnosis.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Diagnosis is important for appropriate management of VWD, and thereby for minimizing the burden of bleeding symptoms and complications on patients and the health care system. 3,9,[14][15][16] Our previous analysis showed that diagnosis of VWD was associated with improved patient outcomes in terms of a lower frequency of bleed claims after (vs before) diagnosis, but that many patients were misrecognized prior to diagnosis. 17 Our present findings, which suggest (based on computer modeling) that there may be a significant number of patients with symptomatic but undiagnosed VWD or other mucocutaneous bleeding disorders within the commercially insured population, underscore the need for continued health care practitioner education to increase VWD detection and diagnosis and are in line with recent calls for improved VWD community education.…”
Section: Implications For Education and Researchmentioning
confidence: 99%
“…Although clinical symptoms are generally milder than in haemophilia, dosing of perioperative treatment in VWD is more challenging due to variation in VWD types and mutations, interpatient variability of residual endothelial VWF production, VWF secretion and clearance, as well as heterogeneity in types of factor concentrates with different ratios of VWF:Act/FVIII and VWF:Act/VWF antigen (VWF:Ag) . Previous studies have, however, reported that surgical procedures can be performed safely in patients with VWD and that treatment with VWF‐containing concentrates is efficacious …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Previous studies have, however, reported that surgical procedures can be performed safely in patients with VWD and that treatment with VWF-containing concentrates is efficacious. [8][9][10][11][12][13][14][15][16][17] In many countries, specific target levels are defined in national guidelines to safeguard haemostasis during surgery. These target values are based on expert opinion and limited observational research ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%